A conserved oligomerization domain in Drosophila Bazooka/PAR-3 is important for apical localization and epithelial polarity. - Benton, R.; St. Johnston, D. (Current Biology, 2003)
The PAR-3/PAR-6/aPKC complex is required to establish polarity in many different cell types, including the C. elegans zygote and epithelial and neuronal cells in Drosophila and mammals. In each context, the components of this complex display a mutually dependent asymmetric cortical localization. PAR-6 is a direct effector of Rho family GTPases and binds to and regulates aPKC. Mammalian PAR-3 (mPar3) can associate with transmembrane proteins and may link the complex to the membrane, but this can account for only part of the requirement for this protein in the complex. Here we investigate the function of a novel conserved domain, CR1, of PAR-3 using computational, biochemical, and genetic approaches. Sequence-structure comparison by FUGUE predicts that CR1 has the same structural fold as a bacterial oligomerization domain. We show that CR1 of the Drosophila homolog, Bazooka (BAZ), mediates oligomerization in vitro and in vivo. Furthermore, deletion of CR1 disrupts BAZ localization in both epithelial cells and the germline and strongly impairs BAZ function in epithelial polarity. These results indicate that this domain is important for the localization and activity of the PAR-3/PAR6/aPKC complex and define a new role for PAR-3 in assembling higher order protein complexes.